Análisis de la redistribución de las regalías en la región caribe a partir de la creación del fondo de compensación regional (2019)
The main reason for the completion of this document is to define whether the redistribution of royalties in Colombia, especially in the Caribbean region, has been effective, through the application of a redistribution of royalties indicator in the previous distribution scheme versus the new distribution of the General Royalty System to know if the departments of that region are receiving more royalties on behalf of the Regional Compensation Fund established by the SGR to finally establish whether said resources derived from the exploitation of non-renewable natural resources are being well executed by the administrations of the departmental mayorships.